Фундаменталізація освіти – потреба часу - Панфілов, Юрій Іванович (НТУ "ХПІ", 2010)
Рассмотрены вопросы необходимости фундаментализации повышения знаний в учебном процессе, соотношения фундаментальных и технологических знаний.

The questions of necessity of fundamentalizion of increase of knowledges in educational process and correlations of fundamental and technological knowledges are considered.
Fundamentalization of education is a requirement of time
Keywords: вища школа; професіонали; конкурентоспроможність; ринок праці; наукові дослідження; якість освіти